Using public comments to gauge social licence to operate for finfish aquaculture: Lessons from Scotland. (1st November 2018) - Billing, Suzannah-Lynn
Abstract: Research and development in the aquaculture industry tends to focus on environmental and economic outcomes. However, with increasing use of marine space, competition between different industries and priorities for coastal communities is a social issue that is coming to the fore. Public perception and local social acceptability have been identified by the industry as key factors in the sustainable growth of finfish aquaculture. With the EU, and the UK and Scottish Governments targeting Blue Growth sectors for development, the drivers of social acceptability issues with finfish aquaculture require attention. Social Licence to Operate (SLO) is a theory which has proved useful in describing the relationship between industry and local communities. This study thematically analyses public comments made on planning applications for new finfish farms in Scotland, and uses SLO theory to explore local scale social interactions and the drivers of public perception of the aquaculture industry. It reveals the complexities of SLO, including areas of concern for engaged members of the public and shows that there are key actors which shape and drive engagement with the debate around whether finfish farms are acceptable. It finds that information used by the public to make decisions around aquaculture is often compiled and distributed by the key actors. This brings into question how much influence local communities have in SLO negotiations. Finally, it reflects that further thought and dialogue within and between research institutes, regulators, industry and local communities is needed to create a more equitable approach to negotiating SLO for finfish aquaculture. Highlights: Social Licence to Operate (SLO) can be determined by analysing public comments. Key agents (individuals) play a significant role in social licence negotiations. There is a lack of non-partial information on finfish aquaculture. There is friction between 'leisure opportunity' and 'livelihood potential'.